MEASURING MEDICATION ADHERENCE THROUGH MOBILE APPS: A SOCIAL SCIENCE PERSPECTIVE - Julia Janecka; Jan Krzysztof Górski; Witold Romuald Gajewski; Weronika Skoczek (International Journal of Innovative Technologies in Social Science, 2025)
Medication adherence is a critical factor influencing the effectiveness of chronic disease management and overall public health outcomes. Despite advances in pharmacotherapy and the availability of effective medications, adherence rates among patients with chronic illnesses remain suboptimal, often as low as 50%, and even lower for asymptomatic conditions such as hypertension. Poor adherence not only reduces the potential benefits of therapy but also contributes to disease progression, increased morbidity, frequent hospitalizations, and substantial financial burdens on healthcare systems. This review provides a comprehensive overview of current methods for measuring medication adherence, including traditional approaches such as self-report, pill count, and clinician assessment, as well as advanced technological solutions like electronic medication packaging (EMP) devices, mobile health (mHealth) applications, video observed therapy (VOT), and ingestible biosensors. The discussion highlights the strengths and limitations of each method, emphasizing that no single approach is flawless and that a multidimensional strategy often yields the most reliable results. Patient-related factors such as knowledge, beliefs, psychological state, and the quality of the patient-provider relationship are identified as key influences on adherence behavior. Socioeconomic variables, cognitive impairment, and regimen complexity further complicate adherence, especially in older adults and vulnerable populations. Recent advances in digital health offer promising avenues for real-time monitoring and tailored interventions, but challenges remain regarding accessibility, cost, user engagement, and data privacy. The review concludes that improving medication adherence may have a more profound impact on public health than developing new therapies. Effective solutions require a holistic approach that integrates reliable measurement, patient-centered care, technological innovation, and system-level support. Ongoing research, collaboration across disciplines, and policy efforts are crucial to bridging the gap between prescribed treatments and real-world patient behavior, ultimately improving health outcomes and reducing healthcare expenditures.